The Powerful of Training; Development and Compensation; Rewards in Sustaining SME’s Performance - Mansor, Mohd Fitri; Abu, Noor Hidayah; Nasir, Hussen (American Scientific Publishers, 2015)
Human capital is one of valuable assets to the organization in order to sustain organization performance and to achieve both employees and employer objectives. The aim of the study is to examine the powerful of both Human Resource practices (i.e. Training & Development and Compensation & Rewards) towards sustaining Small Medium Enterprise’s (SME’s) performance. The objectives of the current study are to examine the relationship between training and development as well as compensation and rewards in sustaining Malaysian Small Medium Enterprise’s performance. Finally, is to identify the strongest variable contribute to the sustainability of Small Medium Enterprise’s performance. The result from 80 Malaysian Small Medium Enterprise’s owners found that both variables training & development and compensation & rewards significantly contributes to the sustainability of Small Medium Enterprise’s performance. Meanwhile, the strongest variable contributes to the sustainability of Small Medium Enterprise’s performance was training and development. The study contributes to the knowledge and awareness to the Small Medium Enterprise’s owners an important or the powerful of human resource practices in sustaining their organization performance